The issue that constraint the procedure of delivering vacant possession with strata title (study case: Penang) / Intan Azrina Mohd Shukri - Mohd Shukri, Intan Azrina (2022)
In Malaysia's housing business, a delay in completing a housing project is typical. In this regard, buyers frequently must accept that 'slower is better than never' is usually the case. The comment referred to the certain buyer receiving the vacant possession with strata title that may have a lot of negative repercussions to them. However, there are various challenges and complications that contribute to the delay in delivering vacant possession with strata title, including the developer, the Licensed Land Surveyor, and JUPEM. This study aims to identify the issues and challenges contributing to the delay in delivering vacant possession with strata title to the buyer. The objectives of this study are to scrutinize the issue that constraint the procedure of delivering vacant possession with strata title and to recommend solution with respect to the late delivery in vacant possession with strata title. This methodology used in this study are quantitative and qualitative method distributed in the interview session to several licensed surveyors and JUPEM in Penang who are contributed to the delays in the process of the delivery vacant possession with strata title. From the interviews, the data are analyzed using pie charts and logistic regression statistical analysis to facilitate the study process where building plan and Proposed Strata Plan (CPS) are the most voted from respondents as it is added significantly to the logistic regression model (CPS (p = .041) and BP (p = .032). Lastly, more experience is needed, more time is needed for architects and JUPEM should contribute in SiFUS level.